Polymers based on benzyl methacrylate: Synthesis via atom transfer radical polymerization, characterization, and thermal stabilities - Demirelli, K; Coskun, M; Kaya, E (Wiley, 2004)
Copolymerization and homopolymerization of benzyl methaerylate (BMA) and ethyl methacrylate (EMA) by the atom transfer radical polymerization method (ATRP) were performed at 90 degreesC. ATRP of BMA was also carried out at 80, 100, and 110 degreesC. The number-average molecular weight (M.) and polydispersities decreased with temperature. When BMA units increased in the copolymer system, the M. values and polydispersities decreased (1.63 < M-w/M-n < 1.13). The homopolymers and poly(BMA-co-EMA) were characterized by Fourier transform infrared (FTIR), H-1 and C-13 NMR, and gel permeation chromatography (GPC) techniques. The compositions of the copolymers were calculated from H-1 NMR spectra. For the atom transfer radical copolymerization system, their monomer reactivity ratios were obtained by using the Kelen-Tudos equation, as r(1) = 0.812, r(2) = 1.162 (r(1) is the monomer reactivity ratio of BMA). The initial decomposition temperatures of the resultant copolymers decrease with an increasing mol fraction of BMA, which indicates that the heat resistance of the copolymer has been improved by decreasing the BMA units. Blends of poly(BMA) and poly(EMA) obtained via the ATRP method have been prepared by casting films from a dichlorormethane solution. The blends have been characterized by differential scanning calorimetry and thermogravimetry. The measurements were comparable with those of copolymers synthesized. (C) 2004 Wiley Periodicals, Inc.
Keywords: ATRP; monomer reactivity ratios; copolymerization; lactone; blends